POSISI PEGADAIAN SYARIâAH DI INDONESIA BERDASARKAN FATWA DSN-MUI NOMOR 25 DAN 26 TAHUN 2002 - Aminuddin, Aminuddin (Al-Mawarid Jurnal Hukum Islam, 2010)
The following article is a research on fatwa National Shariah Council - MUI No. 25 and No. 26 of 2002 as the operational basis of Sharia in Indonesia. From pawnshops this study found that the Fatwa Council of the National Shariah-MUI No. 25 and No. 26 technical bedasarkan determination formulated a fatwa that has been set by the MUI, the review conducted by the Executive Board of the National Shariah Council (BPH-DSN), the result is revealed that fatwa draft form, and then taken in a plenary session of the National Shariah Governing Council to then decide National Fatwa Council to Shariah. Economic realities of society in such a way that demands a lot of different choices of economic services from conventional economic services; community hoping there is certainty of Sharia-based services, particularly in terms of mortgage, and also a request to the Council of Indonesian Ulama Fatwa by conventional economic institutions on economic services that embraces the principles of Sharia.